2010
DOI: 10.1007/s00380-010-0084-2
|View full text |Cite
|
Sign up to set email alerts
|

Elevated B-type natriuretic peptide level as a marker of subsequent thromboembolic events in patients with atrial fibrillation

Abstract: The aim of the present study was to assess whether elevated B-type natriuretic peptide (BNP) levels, as an objective marker of heart failure, is a predictor of subsequent thromboembolic events in patients with atrial fibrillation (AF) during oral anticoagulant therapy. This was a post hoc analysis of a single-center, prospective, observational study. Consecutive patients with AF (261 patients, 74 ± 9 years old, 153 paroxysmal AF) treated with warfarin were included for the analysis. BNP level at baseline exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…In contrast to normally circulating forms of NPs, a mutant form of ANP has been associated with familiar AF [34]. Although the causal relationship between BNP and thrombogenesis remains unknown, studies have reported that high levels of circulating immuno-reactive BNP is associated with increased risk of thromboembolic events [35, 36]. Further studies are needed to investigate whether the observed atrial thrombosis was induced by BNP overexpression or it was primarily related to aging.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to normally circulating forms of NPs, a mutant form of ANP has been associated with familiar AF [34]. Although the causal relationship between BNP and thrombogenesis remains unknown, studies have reported that high levels of circulating immuno-reactive BNP is associated with increased risk of thromboembolic events [35, 36]. Further studies are needed to investigate whether the observed atrial thrombosis was induced by BNP overexpression or it was primarily related to aging.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, D-dimer, which originates from the formation and lysis of cross-linked fibrin and indicates activation of coagulation and fibrinolysis, can be used as a coagulation marker in patients with AF. We reported that D-dimer levels predicted subsequent thromboembolic events in AF patients and that BNP levels (≥200 pg/ml) could be a useful marker for predicting subsequent thromboembolic events in patients with AF during anticoagulant therapy [4,5]. The aims of the present study are to evaluate the association between BNP levels and D-dimer levels and to elucidate the usefulness of measuring BNP levels to provide more information for risk-stratification of AF patients not taking anticoagulant therapy.…”
mentioning
confidence: 91%
“…Their value in a variety of cardiovascular diseases such as myocardial infarction and heart failure have previously been established (80,81). Further studies have also consistently demonstrated that levels of these biomarkers may be used to improve predictions of stroke risk in AF (57,62,(65)(66)(67)71). A RE-LY sub-study found that elevations in troponin I and N-terminal pro-B-type natriuretic peptide (NT-proBNP) were common among AF patients (66).…”
Section: Cardiac Functionmentioning
confidence: 99%